Unimpaired endogenous pain inhibition in the early phase of complex regional pain syndrome. (1st February 2017) - Kumowski, N.; Hegelmaier, T.; Kolbenschlag, J.; Maier, C.; Mainka, T.; Vollert, J.; Enax‐Krumova, E.
Abstract: Background: The complex regional pain syndrome (CRPS) is characterized by distal generalisation of pain beyond the initial trauma. This might be the result of impaired endogenous pain inhibition. Method: We compared Conditioned Pain Modulation (CPM) between patients with CRPS ( n = 24; pain: 4.5 ± 2.2, NRS 0–10; disease duration <1 year), neuralgia ( n = 17; pain: 5.5 ± 1.1) and healthy subjects ( n = 23) and its correlation with loss and gain of function as assessed by Quantitative Sensory Testing (QST). CPM was assessed with heat as test stimulus (TS) and cold water as conditioning stimulus (CS). The early CPM‐effect was calculated as difference between heat pain during and before conditioning, the late CPM‐effect, 5 minutes after and before conditioning, respectively. Results: Heat pain decreased comparably after CS in all groups, resulting in a significant CPM‐effect (healthy: −12.5 ± 12.4, NRS 0–100; CRPS: −14.7 ± 15.7; neuralgia: −7.9 ± 9.8; p < 0.001). When compared to healthy subjects, heat pain declined significantly steeper in CRPS patients (healthy: −2.0 ± 5.5, NRS 0–100/10 s; CRPS: −6.3 ± 8.1; p < 0.05). Only CRPS patients demonstrated a late CPM effect (−6.0 ± 9.0, p < 0.005). Neither spontaneous pain nor any QST parameter correlated with CPM, with the exception of a decreased cold pain threshold, which correlated with an enhanced CPM in CRPS patients only ( r = −0.456, p < 0.05). Conclusion: An impairment of endogenous pain inhibition does not explain the extent of pain in the early stage of CRPS or in neuralgia. The unexpectedly high CPM in CRPS patients might result from activation of the intact descending pathways in response to central sensitization, as cold hyperalgesia correlated with the CPM‐effect. Significance: Conditioned pain modulation (CPM) is not impaired in the early phase of complex regional pain syndrome (CRPS) and neuralgia. Only in CRPS higher CPM was associated with lower cold pain thresholds.